Kegiatan Pengembangan Koleksi Di Dinas Perpustakaan Dan Kearsipan Kabupaten Banyuasin Ditinjau Dari Teori G. Edwards Evans - Gusriani, Moliza; Zulaikha, Sri Rohyanti; Damayanti, Winda (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2023)
Collection development activities are important things to do, especially at the stages of development activities that must be considered and carried out as well as possible. In order to create good service and information needs to users (society). The purpose of this study was to determine the stages of collection development carried out by the Banyuasin Regency Library and Archives Service. In this study, the descriptive qualitative method used data collection techniques through interviews and literature studies, interviews via chat and whatsapp telephone to two librarians at the Banyuasin Regency Library and Archives Service. The results of this study are that the stages of collection development at the Banyuasin Regency Library and Archives Service consist of initial analysis, collection policies, selection of library materials, procurement, weeding and evaluation.